(untitled) (Comprehensive Journal of Science, 2026)
This study offers an analytical reflection on the relationship between stylistics and Arabic rhetoric, aiming to clarify the nature of their connection and to identify points of convergence and divergence between the two approaches. It begins by examining the concept of style and stylistics both linguistically and terminologically, and by highlighting the development and significance of stylistic analysis in modern literary criticism. The study also explores the concept of Arabic rhetoric and its function in textual analysis, particularly its concern with the relationship between wording and meaning, context, and the role of the recipient. The findings indicate that the relationship between stylistics and rhetoric is neither one of complete separation nor total equivalence, but rather one of methodological intersection. While both approaches view discourse as a communicative act, they differ in orientation: rhetoric tends to be normative, whereas stylistics is primarily descriptive and analytical.